Assessing the Impact of Offshore Wind in Massachusetts: An Estimate of C02 Emissions Reductions - Bailey, Ryan. (2018)
Abstract: Massachusetts' Act to Promote Energy Diversity requires distribution companies to solicit contracts for up to 1600 MW of offshore wind. To test whether offshore wind projects can meet the Act's requirement to reduce C02 emissions, the Oak Ridge Competitive Electricity Dispatch Model was used to forecast changes in ISO New England's resource mix under five different wind capacity levels and calculate avoided C02 emissions attributable to offshore wind. With 1600 MW of installed capacity, representing full solicitation under the Act, reliance on natural gas is reduced by ~10% and carbon emissions decline by ~9%. This represents significant progress towards the goals of the Global Warming Solutions Act and the Clean Power Plan. The 5000 MW scenario reduces emissions enough to meet the Clean Power Plan's 2030 goals. This study's application of a dispatch model provides an example for policymakers of a simple and cost-effective approach for assessing a project's value.; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Penn Loh.; Keywords: Energy, Public policy, and Environmental economics.